(3GdNdGUI aj GdMSGHs - (3GdMGQKj GdYGedj GdgePGfj, HgGA GdOjf, eMeO Hf MSjf Hf YHO GdUeO, J (B1031(3g`s
(3ChdgG (B:s
(3fMeOc jG ef dG jMjW HLejY fYeg YOOGYde Cf GdMSGH dG jNai Ydh TCfg hSeh ecGfg hQTGbI eSGFdg hGaJbGQ cKjQ ef GdYdhe hGfYWGa Le ZajQ ef GdeYGedGJ Ydjg hgPg QSGdI aj GdMSGH s
(3BNQgG (B:s
(3hGdSGOS KdGKI eQHYGJ eJfGSHI eLehYgG eQHY hGdSGHY eLPhQ EPG RjO Ydjg LPQg hOQgeGf Ch fbU hGYde CjgG GdCN GdYRjR GdWGdH dfaGFS GdeWGdH Cfj bO GhQOJ Jes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6\102s
(3cTa GdXfhf (B1\720s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdQjGVjGJs